(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Solder paste is widely used by handset repairers who do not use any protective equipment in most developing countries and are exposed daily to the solder paste fumes. The study was conducted to determine the effect of inhalation of solder paste fume on hematological and serum biochemical parameters (Blood Urea Nitrogen and Total Protein) in Wistar rats. A total of forty (40) Wistar rats grouped into experimental and control groups were used. Each rat was exposed to 0.18g of solder paste fume per exposure twice daily (morning and evening) for seven (7) minutes over the period of eight weeks. Blood samples were collected biweekly. The result revealed a statistically significant decrease in Mean Corpuscular Volume (MCV) of the exposed group (63.12 ± 0.56) compared to the control group (65.36 ± 0.53), there was also a significant decrease in total leucocytes count (WBC) (6.01 ± 0.65) in the exposed group compared to the control group (8.56 ± 0.75). However, a significant increase in Mean Corpuscular Hemoglobin (MCH) (22.09 ± 1.4) was observed in the exposed group compared to the control (21.75 ± 0.26). It is concluded that inhalation of solder paste fume have an effect on the hematological profile of Wistar rats.